2016
DOI: 10.1111/jcmm.12741
|View full text |Cite
|
Sign up to set email alerts
|

Telocytes in ileum of the Chinese giant salamander: ultrastructural evidence

Abstract: Telocytes (TCs) and their telopodes (Tps) have been found in various organs of many mammals, including in lower animals. However, knowledge of TCs in lower animals is still very limited. This study identified TCs and their Tps in the ileum of the Chinese giant salamander, Andrias davidianus (Amphibia: Caudata), by transmission electron microscopy. The TCs/Tps were found near epithelial cells, glandular cells and unmyelinated nerve fibres. Moreover, exosomes were also found to be present in between TCs/Tps and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
(24 reference statements)
1
5
0
Order By: Relevance
“…Therefore, to study regeneration mechanisms, lower animals, for example amphibian, may be a better model animal than mammal. Our previous study has confirmed the presence of TCs in the ileum of an amphibian, Chinese giant salamander Andrias davidianus (Amphibia: Caudata) 25 . It is suggested that TCs also may exist in other organs of the amphibian.…”
supporting
confidence: 61%
See 2 more Smart Citations
“…Therefore, to study regeneration mechanisms, lower animals, for example amphibian, may be a better model animal than mammal. Our previous study has confirmed the presence of TCs in the ileum of an amphibian, Chinese giant salamander Andrias davidianus (Amphibia: Caudata) 25 . It is suggested that TCs also may exist in other organs of the amphibian.…”
supporting
confidence: 61%
“…Previous studies also demonstrated that TCs were located in the lamina propria of several animal organs, such as rat duodenum and jejunum, and A. davidianus ileum 4 11 25 . These investigations suggested that TCs may be involved in immune response, intercellular signaling, tissue homeostasis maintenance, and glandular cells secretion and renewal 2 4 11 25 29 . Generally, TCs are suggested to control growth and differentiation of other cell types, mainly stem/progenitor cells, and further regulate surrounding cells regeneration and tissue repair in a particular niche 1 9 30 .…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Consequently, the amount of publications concerning telocytes has grown exponentially (Creoiu & Cretoiu, ). Telocytes are believed to be ubiquitously present and so far have been found in humans and various vertebrate animals such as mice, dogs, chickens and salamanders, where their presence was shown in different organs including heart (Hinescu, Gherghiceanu, Mandache, Ciontea, & Popescu, ; Suciu, Popescu, Regalia, Ardelean, & Manole, ; Gherghiceanu, Manole, & Popescu, ; Popescu et al., ; Yang, Sun, Wu, Xiao, & Kong, ), gut (Cantarero Carmona, Luesma Bartolomé, & Junguera Escribano, ; Cretoiu, Cretoiu, Simionescu, & Popescu, ; Zhang et al., ), liver (Xiao, Wang, Liu, & Yang, ), gallbladder (Hinescu, Ardeleanu, Gherghiceanu, & Popescu, ), parotid glands (Nicolescu, Bucur, Dinca, Rusu, & Popescu, ), exocrine pancreas (Nicolescu & Popescu, ), female reproductive system (Gherghiceanu & Popescu, ; Popescu et al., ; Suciu et al., ; Cretoiu, Cretoiu, & Popescu, ; Hatta, Huang, Weisel, & Li, ; Cretoiu, Cretoiu, Marin, Radu, & Popescu, ), prostate (Corradi et al., ), urinary system (Qi et al., ; Zheng, Zhu, Lin, Wu, & Wang, ; Vannucchi, Traini, Guasti, Del Popolo, & Faussone‐Pellegrini, ), respiratory system (Popescu, Gherghiceanu, Suciu, Manole, & Hinescu, ; Zheng et al., ; Rusu, Jianu et al., ), skin (Ceafalan, Gherghiceanu, Popescu, & Simionescu, ; Rusu, Mirancea et al., ), meninges and choroid plexus (Popescu, Gherghiceanu, Kostin, Ceafalan, & Popescu, ; Xu, Lu, & Zhang, ), skeletal muscle (Popescu, Manole, Serboiu et al., ; Suciu, Popescu, Kostin, & Popesu, ), eyes (Luesma, Gherghiceanu, & Popescu, ), bone marrow (Li, Zhang, Yang, Lu, & Ge, ), vasculature (Li, Lu, Liu, Ge, & Zhang, ), mesentery (Hinescu, Popescu, Gherghiceanu, & Faussone‐Pellegrini, ) and pleura (Hinescu, Gherghiceanu, Suciu, & Popescu, ).…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with mammals, however, there are few investigations of TCs in lower animals. Our previous study has demonstrated the existence of TCs in the ileum of the Chinese giant salamander Andrias davidianus (Amphibia: Caudata) . To determine whether TCs are also present in other organs of the amphibian, further studies are required.…”
mentioning
confidence: 99%